Patient characteristics of Medicare beneficiaries who report not getting influenza and pneumococcal vaccinations, 2001–2013. Issue 5 (3rd May 2020) - Shen, Angela K.; Warnock, Rob; Selna, Weston; Chu, Steve; Kelman, Jeffrey A.
ABSTRACT: Background : Despite long standing recommendations of pneumococcal and influenza vaccination for adults age 65 years and older and wide-spread availability to vaccination services, vaccination coverage in the United states is low. We sought to explore reasons patients reportedly did not receive these vaccines. Methods : We used publicly available data from the Medicare Current Beneficiary Survey, a continuous panel survey of a representative sample of the Medicare population, as well as Medicare enrollment data. We explored questions pertaining to influenza and pneumococcal vaccination status, self-reported reasons for being unvaccinated and patient perspectives toward health care utilization. Results : The majority of the respondents who did not receive vaccines for influenza or pneumococcal disease reported that they did not know it was needed or that their doctor did not recommend it. Respondents who were not vaccinated against influenza reported concerns about side effects. Coverage for both vaccines was lower among respondents in the Southeast region and among those who are dual-eligible or less engaged in healthcare utilization. Little difference was observed by gender, urban status, or Part C enrollment for influenza respondents. Higher pneumococcal vaccine coverage was found among females as well as those living in urban settings or enrolled in Medicare Part C. Conclusions : Implementation of the national guidelines calling for all health care professions – whether they provide vaccinations or not – to take steps to help ensure adults are fully immunized is critical. Tailored communication to beneficiaries that addresses the importance of both vaccines as well as key barriers, like side effects, is also needed.